Analysis of the extracorporeal anticoagulation effect of modified citrate infusion during continuous renal replacement therapy in critically ill patients. Issue 2 (27th September 2022) - Guo, Litao; Liu, Yu; Zheng, HaiRong; Shi, Qindong; Wang, Gang
Abstract: Introduction: To analyze the anticoagulation effect of different local infusion methods of citrate underwent continuous renal replacement therapy (CRRT) in critically ill patients. Methods: The study adopted a single‐centre retrospective design. Critically ill patients were divided into conventional group and modified group based on the infusion methods of citrate. Results: The modified group had a longer mean treatment time (67.67 ± 18.69 hours vs. 52.11 ± 24.26 hours, p = 0.007), a lower transmembrane pressure (147.77 ± 66.85 cm H2 O vs. 200.63 ± 118.66 cm H2 O, p = 0.038), fewer citrate bag replacements (1.43 ± 0.50 times vs. 10.60 ± 3.19 times, p < 0.001), and more steady ionized calcium at the venous end (0.35 ± 0.06 mmol/L vs. 0.40 ± 0.05 mmol/L, p = 0.006) compared to the conventional group patients, with statistically significant differences. The incidences of citrate accumulation and tubing coagulation were marginally lower in the modified group. Conclusion: The modified local citrate infusion method can prolong treatment time, while reducing both the nursing workload and the occurrence of citrate accumulation.